PSYCHOPHYSIOLOGICAL EFFECTS OF REAL AND FICTICIOUS STRESS IN BOTH A-TYPE AND B-TYPE SUBJECTS - Palmero Cantero, Francisco; Breva Asensio, Alicia; Espinosa, Matilde (Anales de Psicología / Annals of Psychology)
Though the Tipe A behavior pattern has been very criticized, perhaps some of its components can be reliable to investigate as psychological variables affect the cardiovascular diseases. In this study, the S factor was used too form two groups and to observe psychophysiological activation, reactivity and recovery in two tasks: real and ficticious stress. Results showed a higher values in the physiological activation, reactitivy and recovery in both groups in the real stress situation. It can also be observed that Type A subjects point out higer values than Tipe B subjects. It is suggested that real stress tasks should be used to establish the accurate of psychophysiological profile in Type A and Type B subjects. We propose that the “fast activation-slow recovery” profile is characteristic of Type A scores. The “fast activation-fast recovery” profile is characteristic of Type B.